Capacidade contributiva como limite à liberdade de conformação do legislador em impostos extrafiscais de finalidade ambiental: uma análise jusfundamental - Dantas, Eric de Moraes (2013)
This study analyzes, whether and how the tax-paying ability principle interpreted through the prism of fundamental rights theories, can influence the freedom of conformation of the legislature in using the extrafiscality of taxes for environmental purposes. States as initial hypothesis, the possibility that tax-paying ability principle has to limit that freedom of conformation through the need for a quantitative link between the tax quantitative elements and (im)possibility of objective measurement of some economic criteria that is connected to a situation to promote the environment through a tax relief, even if from this criteria is the economic capacity only indirectly recognized. Develops five minor hypotheses in reference to the interpretation of tax-paying ability principle, which: 1) is not an immanent limit extracted from the Constitution, although in certain situations influences the freedom of conformation of the legislator in extrafiscal environmental taxes; 2) can be recognized from the Brazilian Constitution, as restrictive clause of the fundamental right to an ecologically balanced environment or as 3) element of interference in the process of configuration of such right. Wonders also if this principle: 4-) must always be present in the factual support of environmental taxes norms, which makes it peculiar (peculiar factual support of environmental tax norms), so it can appear as a previous element, or even complementary, to be taken into account against the proportionality test applied in the exam of limits of restrictions to the fundamental rights of the taxpayer; or 5) limits the freedom of the legislator in the process of conforming environmental taxes norms, because the inherent rights to their content have itself the capability to promote restrictions on the right to the environment in certain situations. Conjugate a third element to the economics and to the merely ethical theories about the paying-tax ability, the legal one, which is analyzed by the fundamental rights perspective. Distinguishes between causal theories and merely ethical theories about that principle. Expounds the juridical content of tax-paying ability principle in a didactic way, which provides through the perspective of fundamental rights theories the elements to correlate it to the extrafiscality in environmental taxes. Discusses the several theories of fundamental rights and explains the reasons of the failure in adopting an internal theory in order to elaborate this study. Provides the reasons that motivated the option for external theory, which are the same causes for the hypothesis 1 acceptation. After highlights the complementarity between extrafiscality and ability to pay. After the demonstration of the complementarity between extrafiscality and tax-paying ability, outlines the reasons for adopting the external theory to the explanation and explains the causes for rejecting hypothesis 1, which are basically the same for not using the internal theories in the research. Ascertains the viability of hypotheses 2 and 3, covering, respectively, the ability to contribute as a restrictive clause on the right to the environment and as a configuration parameter to this same right. Comments the possibility of limiting the freedom of conformation of the legislature in using the taxes extrafiscality for environmental purposes, emphasizing especially the controls of constitutionality; of constitutionality of the law that assigns powers of amendment to the quantitative elements of the tribute to the Public Authorities, of the forth and fifth hypothesis and of legality. At last but not least, justifies the initial proposal, demonstrating the need for a quantitative link between the tax and economic criteria that maintains pertinence to the situations that has received tax relief in order to foster the extra fiscal purpose. Distinguishes also this very last control form from the other one in which taxes are graduated based merely on aspects of the taxpayer and as well from that another one of proportionality.